2019
DOI: 10.1016/j.ijdevneu.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Degree centrality of key brain regions of attention networks in children with primary nocturnal enuresis: A resting‐state functional magnetic resonance imaging study

Abstract: Primary nocturnal enuresis (PNE) is always associated with attention impairment, some of which even could develop to attention deficit hyperactivity disorder. The mechanism of attention impairment is not clear, especially lacking of objective indicators of neuroimaging. The aim of this study is to explore the possible functional imaging mechanism of impaired attention in PNE children. A total of 26 PNE children and 26 age-matched normal controls were recruited. Resting-state functional magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Subsequently, they performed another study with regard to the DC of key cerebral areas of attention networks in nocturnal enuresis, in which pediatric patients showed remarkable attention deficits and the DC values were reduced in the right inferior parietal sulcus, temporoparietal junction, right frontal eye field, left angular gyrus, and left inferior parietal sulcus. 65 Therefore, dysfunctions in these cortices may be responsible for the impaired attention in children with nocturnal enuresis. Recently, this group also found that the ALFF values were increased in the bilateral medial prefrontal cortex, left inferior temporal gyrus, and anterior cerebellum lobe, but decreased in the left middle temporal gyrus in the children with attention deficit hyperactivity disorder (ADHD).…”
Section: Brain Functional Imaging In Nocturnal Enuresismentioning
confidence: 99%
“…Subsequently, they performed another study with regard to the DC of key cerebral areas of attention networks in nocturnal enuresis, in which pediatric patients showed remarkable attention deficits and the DC values were reduced in the right inferior parietal sulcus, temporoparietal junction, right frontal eye field, left angular gyrus, and left inferior parietal sulcus. 65 Therefore, dysfunctions in these cortices may be responsible for the impaired attention in children with nocturnal enuresis. Recently, this group also found that the ALFF values were increased in the bilateral medial prefrontal cortex, left inferior temporal gyrus, and anterior cerebellum lobe, but decreased in the left middle temporal gyrus in the children with attention deficit hyperactivity disorder (ADHD).…”
Section: Brain Functional Imaging In Nocturnal Enuresismentioning
confidence: 99%
“…In addition, abnormalities of local brain activity in mPFC have been identified in extensive studies and may be related to the cortical control mechanisms of PNE ( Lei et al, 2012b ; Schulz-Juergensen et al, 2013 ; Zhu et al, 2019 ). Besides abnormalities of local brain activity, the key brain regions of DMN, dorsal attention network (DAN), and ventral attention network (VAN) were damaged and likely related to attention impairment in children with PNE ( Jiang et al, 2019 ). The simple model of the lower urinary tract (LUT) control presented by Griffiths demonstrated that the DMN and SN are two crucial brain networks to sustain continence ( Griffiths, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to involvement of bladder sensation, the insula is also engaged in working memory ( Cai et al, 2021 ), decision-making ( Loued-Khenissi et al, 2020 ), interoception ( Chen et al, 2021 ), state switching ( Menon and Uddin, 2010 ), and emotional process ( Gasquoine, 2014 ). Based on prior functional MRI (fMRI) studies ( Zhang et al, 2015 ; Jiang et al, 2019 ; Wang et al, 2019 ), children with PNE also have potential impairments in working memory, attention cognition, and emotional responses.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent was obtained from the parent of each participant, and all the children agreed to participate in the study. The comparison of IQ between the NE and control group was done by two‐sample t ‐test, and no statistical difference was found so as to exclude the influence of IQ on cognition (Table 1) (Jiang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The question remains how these brain regions affect attention function in children with enuresis. In a previous study, we extracted the degree centrality values of these network key brain areas for comparative study and found that abnormalities in brain areas such as the right frontal eye field, bilateral inferior parietal sulcus and left angular gyrus were related to impaired attention in children with NE (Jiang et al, 2019). However, the study was only an analysis of individual brain regions, not the FC between those regions.…”
Section: Introductionmentioning
confidence: 99%